PENGEMBANGAN MODUL PEMBELAJARAN MODEL DICK & CAREY MATERI TAFSIR EMANSIPATORIS DALAM UPAYA DERADIKALISASI MAHASISWA PERGURUAN TINGGI AGAMA ISLAM DI INDONESIA - Umarella, Samad; Lasaiba, Irvan (IAIN Ambon, 2021)
In recent decades, Indonesia has witnessed a concerning rise in radical actions, with various acts of violence frequently making headlines despite the government's efforts to foster a harmonious society. Radical groups come from diverse backgrounds, including ethnic and religious affiliations, with religious extremism often seen as the dominant force behind violent incidents. These conflicts, including those with religious motives, continue to emerge even within communities that uphold diversity and coexistence. In response, the development of an Emancipatory Tafsir Module seeks to help deradicalize students in Islamic higher education institutions by providing structured learning materials for Qur’anic Interpretation (Tafsir) courses. This initiative follows five key steps: (1) selecting the relevant course, (2) analyzing the syllabus, (3) defining clear learning objectives, (4) creating effective instructional strategies, and developing a comprehensive module. The module itself includes essential components such as a (a) concept map, (b) learning objectives, (c) lesson plans, (d) study materials, (e) summaries, (f) evaluations, and (g) references. (5) Finally, it undergoes expert review by specialists in Islamic education, Qur’anic studies, linguistics, and instructional design to ensure its effectiveness in promoting critical thinking and preventing radicalization among students.